Model Berbasis Portofolio untuk Meningkatkan Partisipasi Belajar Siswa pada Pembelajaran PKN - Hasnawati Hasnawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2017)
At SDN 11 Batang Anai, participation of 4th grade students in civic learning was low, either in discussing, asking question, or taking conclusion. Teacher used to implement expository method in classroom. This study is a classroom action research that aimed to improve students’ participation in learning civic subject by using model of portfolio-based. In cycle I, percentage of students’ participation for discussing is 58.92%, 49.80% for asking question, and 33.92% for taking conclusion. In cycle II, percentage of students’ participation for discussing is 84.45%, 72.73% for asking question, and 70.95% for taking conclusion. Hence, civics learning that implement model of portfolio-based can improve students’ participation in learning.